(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Textile industrial activities have been characterized in its usage of large volumes of water and variety of chemicals. Surface-active chemical compounds produced by vast varieties of microbial species are known as biosurfactant. This study aimed at screening of biosurfactant-producing Pseudomonas and Bacillus species isolated from engine oil contaminated soil for biodecolorization of textile effluents. Engine-oil polluted soil sample was collected from a mechanic work shop in Abakpa Kaduna state. Bacteria from oil polluted soil was isolated by standard spread plate technique. Physical properties of the effluent sample were determined. Screening of isolates for biosurfactant production potential was achieved using standard method. The PCR amplification of the isolates was carried out using 16S rDNA primers. The results obtained revealed that Bacillus had the highest frequency of occurrence (26.6%), followed by Micrococcus, Pseudomonas and Staphylococcus (20% each) while Acinetobacter had (13.3%). isolate S9 had the highest emulsification index (52.5%). On the other hand, isolate S11 had the lowest emulsification index (44.8%). Pseudomonas aeruginosa S5 had 99% homologue with Pseudomonas aeruginosa MSSRFV220 while Bacillus subtilis S5 had 75.59% homologue with Bacillus subtilis BC5. Textile effluent with 1.0 mg of biosurfactant from Pseudomonas aeruginosa had the highest pH value (8.0) while textile effluent with 1.0 mg of biosurfactant from Bacillus subtilis recorded the least pH value (7.6). Textile effluent amended with biosurfactant from Bacillus subtilis showed a higher temperature value (37oC) while the least temperature value was (33oC). It is concluded therefore, that Bacillus and Pseudomonas species are good biosurfactant producers.